Investigation Of an Outbreak of Diphtheria in Dabela Village of Amirgagh Taluka and CHC, Banas kantha, Gujarat (Current Scenario) - Talsania, Niti; Chauhan, Jignesh; Nayak, Himanshu; Shah, Chintul; Modi, Krunal; devaliya, Jaydeep (National Journal of Community Medicine, 2011)
As outbreak of diphtheria reflects the impact of immunization outbreak investigation was carried out to assess the diphtheria outbreak pattern and case fatality rate in Dabela Village of Amirgagh Taluka and CHC, District, Banaskantha, Gujarat in 2007. Population stabilization, poverty alleviation, life-style modification, surveillance and control of communicable and non-communicable diseases constitute the major challenges demanding urgent attention in the future. Vaccine was efficacious among those who received >4 doses. The proportion of the population receiving boosters was low, especially among Muslims. We recommend increasing booster dose coverage. We investigated epidemic to 1) describe the epidemiology of diphtheria in terms of time, place, and person; 2) estimate vaccine coverage; and 3) to do SWOT analysis in Immunization services.4) To suggest successful vaccination.